2022
DOI: 10.1021/acsami.2c03370
|View full text |Cite
|
Sign up to set email alerts
|

Titration of Cu(I) Sites in Cu-ZSM-5 by Volumetric CO Adsorption

Abstract: Cu-exchanged zeolites are widely studied materials because of their importance in industrial energetic and environmental processes. Cu redox speciation lies at the center of many of these processes but is experimentally difficult to investigate in a quantitative manner with regular laboratory equipment. This work presents a novel technique for this purpose that exploits the selective adsorption of CO over accessible Cu(I) sites to quantify them. In particular, isothermal volumetric adsorption measurements are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 64 publications
(89 reference statements)
0
15
0
Order By: Relevance
“…The slope of the scatter plot linear fit ( Figure S9 ) indicated that . This approach is conventionally used for determining ε of adsorbed species [ 62 , 63 , 64 , 65 ]. In contrast, this is so far the first attempt to evaluate the Ce 3+ molar extinction coefficient and it could potentially be used in the future to evaluate Ce 3+ concentration from FT-IR measurements.…”
Section: Resultsmentioning
confidence: 99%
“…The slope of the scatter plot linear fit ( Figure S9 ) indicated that . This approach is conventionally used for determining ε of adsorbed species [ 62 , 63 , 64 , 65 ]. In contrast, this is so far the first attempt to evaluate the Ce 3+ molar extinction coefficient and it could potentially be used in the future to evaluate Ce 3+ concentration from FT-IR measurements.…”
Section: Resultsmentioning
confidence: 99%
“…All the samples have been well characterized with techniques like XRD, SEM, elemental analysis, and N 2 -physisorption, in previous publications. 9,10 The relevant elemental composition and the samples corresponding activity in the methane to methanol (MTM) conversion is reported in Table S1 in the ESI †. In this fundamental study, we report a new pathway for ethane conversion over Cu-zeolites, and we explore the structural and compositional requirements for an effective reaction.…”
mentioning
confidence: 99%
“…35 Another fascinating example is the complexation of Cu + ions in Cu-ZSM-5 by CO, forming homogeneous-like structures where the metal ion is partially detached from the framework. 8,36,37 Keeping in mind this knowledge about metal ions in zeolite, this perspective deals with the recent ndings about mobilization of Cu ions in zeolites under reaction conditions, with particular attention to the role of reactants and ligands on the ions redox properties and reactivity in the two most studied reactions over Cu-zeolites in recent years: the Selective Catalytic Reduction of NO x mediated by NH 3 (NH 3 -SCR) and the direct conversion of methane to methanol (DMTM).…”
Section: Introductionmentioning
confidence: 99%
“…35 Another fascinating example is the complexation of Cu + ions in Cu-ZSM-5 by CO, forming homogeneous-like structures where the metal ion is partially detached from the framework. 8,36,37…”
Section: Introductionmentioning
confidence: 99%